Factors Associated With Multi-Drug Resistant Organisms Among Bronchiectasis Patients: A Retrospective Study of Bronchiectasis Patients in Jordan - Al Oweidat K; Toubasi AA; Khraisat FA; Al-Sayegh TN; Al-Harasis LM; Albtoosh AS (International Journal of General Medicine)
Khaled Al Oweidat,1 Ahmad A Toubasi,2 Farah A Khraisat,2 Thuraya N Al-Sayegh,2 Layla M Al-Harasis,3 Asma S Albtoosh1 1Department of Respiratory and Sleep Medicine, Department of Internal Medicine, School of Medicine, The University of Jordan, Amman, Jordan; 2Faculty of Medicine, The University of Jordan, Amman, Jordan; 3Faculty of Medicine, the Jordan University of Science and Technology, Irbid, JordanCorrespondence: Ahmad A Toubasi, Faculty of Medicine, the University of Jordan, Amman, 11942, Jordan, Tel +962798035061, Email tubasi_ahmad@yahoo.comBackground: Bronchiectasis, a respiratory ailment, significantly impacts the life expectancy of individuals. This study aimed to explore the prevalence of multidrug-resistant organisms (MDROs) among bronchiectasis patients, the resistance patterns within various antibiotic classes, and the associated factors with these organisms.Methods: A retrospective observational analysis was conducted on adult bronchiectasis patients attending clinics at Jordan University Hospital. The diagnosis of bronchiectasis was established through lung Computerized Tomography (CT) scans and clinical symptom assessment.Results: The study encompassed 235 patients, revealing a notably higher occurrence of MDROs among non-cystic fibrosis patients compared to their counterparts (P-value=0.001). Additionally, MDROs showed significant associations with the usage of inhaled beta agonists, anti-cholinergics, corticosteroids, and inhaled antibiotics (P-value< 0.050). Patients with MDROs experienced a significantly elevated mean number of hospitalizations, exacerbations, and antibiotic courses compared to their counterparts (P-value< 0.050). Moreover, those with MDROs exhibited a higher incidence of requiring O2 device support and faced an increased risk of mortality (P-value< 0.050).Conclusion: The observational nature of our study limits the associations in our study. However, we provided evidence that it is imperative for clinicians to assess their bronchiectasis patients for MDRO risk factors, facilitating appropriate initial antibiotic selection. Nevertheless, the validation of MDRO risk factors necessitates further exploration through larger studies with extended follow-up periods.Keywords: human, respiratory diseases, bronchiectasis, antibiotic resistance, microbiology